Environmental Hazard: The Legal Issues Concerning Environmental Justice in Nigeria - Paul Atagamen Aidonojie (Lembaga Contrarius Indonesia, 2023)
One of the challenges the global community seeks to solve is environmental hazards emanating from human harmful activities. Although, Nigeria seems to be part of the global authors seeking environmental justice concerning environmental hazards, however, the incidence of environmental hazards seems to be very pronounced, given the ineptitude of environmental justice towards victims of an environmental hazard. It is concerning this that this study tends to embark on a hybrid method of study in ascertaining the current state of environmental hazard in Nigeria and the challenges concerning environmental justice. The study further found that the continuous environmental hazard in Nigeria is a result of the ineptitude of environmental justice toward the victim of an environmental hazard. The study therefore concludes and recommends that for an effective curtailing of the incidence of environmental hazards in Nigeria, the Nigerian government needs to intensify justice for the victim of environmental hazards and ensure the predators of environmental hazards are legally constricted from their continuous harmful activities.